Caracterização dendrométrica e crescimento de dez espécies florestais nativas em plantios homogêneos no estado do Espírito Santo - Martins, Leandro Tose (2012)
This study aimed to produce information dendrometric and growth of ten native species subjected to homogeneous plantations. The species considered in this study were paraju (Manilkara bella Monach.) jequitibá rosa (Cariniana legalis (Mart.) O. Ktze), gonçalo alves (Astronium concinnum (Engl.) Schott), ipe felpudo (Zeyhera tuberculosis (Vell.) Bur), tarumã (Vitex sp.) guaribu amarelo (Taub Goniorrachis marginata), nagibe (Kielmeyera albopunctata Saddi), farinha seca (Pterygota brasiliensis), sapucaia vermelha (Lecythis pisonis Cambess), and cajá (Spondias purpurea L.). The data used are from plantations Reserva Natural Vale, located in Linhares in northern Espírito Santo. The plantations of each species were deployed at a spacing of 2mx2m. Each species was characterized by calculating variables such as arithmetic mean diameter, quadratic mean diameter, mean height, basal area and form factor. For paraju basic density was determined to 7 trees of different classes of diameters and also the density for each tree at positions corresponding to 0%, 25%, 50% and 75% of commercial height. For the same trees used for the calculation of the density were determined the levels of Carbon, Hydrogen and Oxygen. Were fitted five hypsometric models, five volumetric models, and two growth models for the diameter and height as a function of age and were later given the increases in diameter and height for each species. After careful analysis of the data it was observed that the species showed large variation in the variables analyzed dendrometric. The mean basic density of 0.745 g/cm3 was paraju. It was found that the density values paraju basic density decreased along the stem towards the base / top. The carbon content was found to be 44.49%, hydrogen was 6.53% and nitrogen was 0.25%. The hypsometric models were selected as model 5 that best explains the variations in height for the paraju, jequitibá rosa, sapucaia vermelha, gonçalo alves. As for the other species (ipe felpudo, tarumã, guaribu amarelo, cajá, farinha seca, nagibe) the selected model was the fourth. To explain the variations in volume were selected for the models Stoat paraju, sapucaia vermelha, the Schumacher and Hall for the guaribu amarelo caja, the Husch to farinha seca, to Ogaya for ipe felpudo, gonçalo alves and Spurr of the linear jequitibá rosas, trauma and nagibe. To explain the growth in diameter and height were selected for the logistic model 9 of the 10 species evaluated. Only tarumã was selected for the exponential model. Cajá followed by farinha seca were the species that grew better diameter and height when compared to the other. The species with lower growth was tarumã